Peran Loyalitas Karyawan dalam Memediasi Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan - Sri Sundari; Mayla Surveyandini; Herwiek Diyah Lestari (Majalah Imiah Manajemen & Bisnis, 2022)
This study aims to analyze the effect of leadership style on employee loyalty and employee performance. This research was conducted on employees of PT. Cogindo Daya Bersama at the Adipala Unit. The sampling technique in this study was proportional random sampling, and the method of analysis used multiple linear regression analysis and the Sobel test. Based on the results of data analysis, it can be interpreted that leadership style has a significant positive effect on employee loyalty, leadership style and employee loyalty have a significant positive effect on employee performance, and employee loyalty mediates the influence of leadership style on employee performance. The implication that can be made is that companies need to implement appropriate policies related to leadership style and loyalty to improve employee performance. These motivating ways can be done by focusing on efforts to continuously improve the ability of company managers to establish communication with various parties, improve the ability of managers in employees and continue to increase employee confidence so that the management of PT. Cogindo Daya Bersama at the Adipala Unit was able to live up to their expectations.